A Survey on the Use of Personalized Model-Based Search Engine - Mahdi M.N.; Ahmad A.R.; Qassim Q.S.; Subhi M.A.; Bakare T.A. (Springer Science and Business Media Deutschland GmbH, 2023)
Mostly with growth of the information sector, in particular the World wide web and the mobile Internet, the volume of information that well have to contend with is rapidly increasing. To a certain degree, users could get the information they need from the Internet. And in context of these vast availability and proliferation of information, users need an efficient way of finding only important and interesting information. How to optimize usability during information search process is still not addressed. Searching was the key feature of a conventional search engine. There has been insufficient customization in search engines to be used by searchers during the information extraction process. This article thus analysed and discussed the personalized recommendations of searches using a tailored framework that supports search engines. We describe a comprehensive review of the study on search engine customization for web-based queries. The study is partially systematic and, also at end of the study, we discuss the difficulties of personalizing search engines. 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.